2021
DOI: 10.1038/s41893-021-00729-z
|View full text |Cite
|
Sign up to set email alerts
|

Massive soybean expansion in South America since 2000 and implications for conservation

Abstract: A prominent goal of policies mitigating climate change and biodiversity loss is to achieve zero-deforestation in the global supply chain of key commodities, such as palm oil and soybean. However, the extent and dynamics of deforestation driven by commodity expansion are largely unknown. Here we mapped annual soybean expansion in South America between 2000 and 2019 by combining satellite observations and sample field data. From 2000–2019, the area cultivated with soybean more than doubled from 26.4 Mha to 55.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
137
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 244 publications
(147 citation statements)
references
References 50 publications
2
137
0
8
Order By: Relevance
“…Previous studies have shown that soybean production plays an important role in the economic development of soybean producing regions 31 , 32 , 49 , although with varying effects according to the region considered. For instance, soybean production exhibited a positive effect on socioeconomic metrics such as the Gini coefficient for income in the new agricultural frontier of the Amazon biome and MATOPIBA (northeast region within the Cerrado biome 49 ), while in Mato Grosso no such effect was found 32 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that soybean production plays an important role in the economic development of soybean producing regions 31 , 32 , 49 , although with varying effects according to the region considered. For instance, soybean production exhibited a positive effect on socioeconomic metrics such as the Gini coefficient for income in the new agricultural frontier of the Amazon biome and MATOPIBA (northeast region within the Cerrado biome 49 ), while in Mato Grosso no such effect was found 32 .…”
Section: Discussionmentioning
confidence: 99%
“…The soybean production of a given year requires previous years of preparation, which involves soil preparation, land-use and land-cover (LULC) changes, access to credit and financial resources, labor, thereby a set of situations to favor its success 27 , 28 , 33 . However, after the crop starts developing in a given area and year, other dynamics are expected to occur as a consequence, which may lead to different socioeconomic and environmental outcomes 31 . Given Tobler’s first law of geography 51 we hypothesized that the effects of the soybean production in a region will influence neighboring areas through path dependencies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These contributions typically use supply side models at the national level and downscale national trade or production data at the locallevel. Our approach has several advantages: it is less data-demanding 1 ; it is agnostic in terms of scale of agricultural production contrary to contributions based on spatial attribution or classifications methods [10,28] that oppose large scale commodity driven deforestation to shifting agriculture 2 ; it uses a sample based on forested areas at the beginning of the study period, rather than deforested areas at the end of the period, which facilitates causal interpretation; and it does not suffer from leakage effects since it is not limited to a single crop or geography [35].…”
Section: Introductionmentioning
confidence: 99%
“…It includes replacement of family farming, secondary vegetation, and pasture by monoculture. Areas of primary forest were advanced, thus increasing deforestation (Song et al 2021;Coelho 2009).…”
Section: Introductionmentioning
confidence: 99%